Predicting formative feedback practices: improving learning and minimising a tendency to ignore feedback - Brown, Gavin T. L.; Andersson, Catarina; Winberg, Mikael; Palm, Torulf (Frontiers in Education, 2023)
Teacher conceptions of feedback ideally predict their feedback practices, but little robust evidence identifies which beliefs matter to practices. It is logical to presume that teacher conceptions of feedback would align with the policy framework of an educational jurisdiction. The Teacher Conceptions of Feedback (TCoF) inventory was developed in New Zealand which has a relatively low-stakes, formative policy framework. This study surveyed 451 Swedish teachers working in Years 1-9, a policy context that prioritises teachers using multiple data sources to help students learn. The study used a translated version of the TCoF inventory, but isolated six items related to formative feedback practices from various factors. A six-factor TCoF was recovered (Praise, Improvement, Ignore, Required, PASA, and Timely), giving partial replication to the previous study. A well-fitting structural equation model showed formative practices were predicted by just two conceptions of feedback (i.e., feedback improves learning and students may ignore feedback). This study demonstrates that the TCoF inventory can be used to identify plausible relations from feedback beliefs to formative feedback practices.